CANDELS multi-wavelength catalogs: source identification and photometry in the CANDELS Extended Groth Strip - Stefanon, Mauro; Yan, Haojing; Mobasher, Bahram; Barro, Guillermo; Donley, Jennifer L.; Fontana, Adriano; Hemmati, Shoubaneh; Koekemoer, Anton M.; Lee, BoMee; Lee, Seong-Kook; Nayyeri, Hooshang; Peth, Michael; et al. (American Astronomical Society, 2017)
We present a 0.4-8μm multi-wavelength photometric catalog in the Extended Groth Strip (EGS) field. This catalog is built on the Hubble Space Telescope (HST) WFC3 and ACS data from the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS), and it incorporates the existing HST data from the All-wavelength Extended Groth strip International Survey (AEGIS) and the 3D-HST program. The catalog is based on detections in the F160W band reaching a depth of F160W=26.62 AB (90% completeness, point-sources). It includes the photometry for 41457 objects over an area of ~ 206 arcmin2 in the following bands: HST ACS F606W and F814W; HST WFC3 F125W, F140W and F160W; CFHT/Megacam u∗, g′, r′, i′ and z′; CFHT/WIRCAM J, H and KS; Mayall/NEWFIRM J1, J2, J3, H1, H2, K; Spitzer IRAC 3.6μm, 4.5μm, 5.8μm and 8.0μm. We are also releasing value-added catalogs that provide robust photometric redshifts and stellar mass measurements. The catalogs are publicly available through the CANDELS repository.